Development of a Structural Model of Love Trauma Syndrome Based on Emotional Intelligence Mediated by Cognitive Distortion in Adolescent Girls Experiencing Emotional Grief - Meysami Azad, Shiva; Pirani, Zabih; Taghvaei, Davood (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to develop a structural model of love trauma syndrome based on emotional intelligence with the mediating role of cognitive distortion in adolescent girls experiencing emotional grief. Methods and Materials: This fundamental and correlational study employed a structural equation modeling (SEM) approach within a positivist paradigm and a cross-sectional design. The statistical population consisted of 11,894 female high school students in Arak during the 2022–2023 academic year. A sample of 300 participants who had experienced romantic breakup was selected using purposive sampling. Standardized instruments were utilized, including the Love Trauma Syndrome Scale (Ross, 1999), the Emotional Intelligence Questionnaire (Schutte et al., 1998), and the Cognitive Distortion Questionnaire (Abdollahzadeh & Salar, 2010). Content and construct validity were confirmed, and reliability was assessed using Cronbach’s alpha, composite reliability (CR), and McDonald’s omega, all of which exceeded 0.70. Data were analyzed using SPSS-27 and AMOS-20 software through descriptive statistics, Pearson correlations, and structural equation modeling. Findings: The results revealed a significant negative relationship between emotional intelligence and love trauma syndrome (p < 0.01), as well as between emotional intelligence and cognitive distortion (p < 0.01). Additionally, cognitive distortion was positively associated with love trauma syndrome. Mediation analysis indicated that cognitive distortion significantly mediated the relationship between emotional intelligence and love trauma syndrome (β = -0.321, CI 95% = -0.548 to -0.210), with bootstrapping confirming the significance of the indirect effect. Conclusion: The findings support a structural model in which emotional intelligence directly and indirectly (via cognitive distortion) influences love trauma syndrome in adolescent girls. The results highlight the importance of emotional and cognitive regulation in adolescent emotional resilience.